(untitled) (ETNOSIA : Jurnal Etnografi Indonesia, 2017)
Wahdah Islamiyah (WI) is a community organization (ormas) based in Makassar under the aupices of Yayasan Pesantren Wahdah Islamiyah (YPWI). Members of WI are the followers of Salafi, a social movement which tries to practice Islamic values according to the understanding of As-Salaf As-Shalih. While members of WI consists of men and women, this article is focused on how female members of WI practice the ideal values of womenhood set by WI in the every day life. The research findings indicates that members of WI consist of three categories, namely: new members, teachers (murabbi), and administrative staff of its Lembaga Muslimah WI. The value of womenhood is set by the organization, and is classified into three, namely how to dress properly, how women behaves towards the opposite sex, and how ‘to become a wife/mother’. The application of such values is not always syncronised with the ideal ones, depending on their level of membership and which value and which condition faced by the members. While new members tend to have a space for negotiation; murabbi is more advance than new members in the practice of womenhood values, which can be seen from how they dress (ber-hijab) and how they interact with the opposite sex; staff of Lembaga Muslimah WI is focused on how to practice such values in relation to how ‘to become a wife/mother’. Thus, women transform themselves spiritually on the basis of womenhood values as they become part of the organization and the level of their membership.